The Study of the three Applications of Infinitude in the Islamic Theology and Philosophy and its Ascription to Allah - javad Ja’efariyan; mohammad mahdi Gorjiyan (حکمت اسرا, 2014)
Although apparently Allah’s infinitude seems to be an obvious matter, some believe that the belief in the infinitude of Allah in all of the arenas, the divine Names and Attributes, is inconsistent with the analogical and revealed principles. The present paper seeks to demonstrate that the correct view of the infinitude of Allah is the “infinite existential interpretation”, by examining and criticizing three different interpretations of infinitude, thus, proving that those who deny the infinitude of Allah are mistaken in their interpretations of concept of infinitude. Moreover, it seeks to answer the existing doubts in this regard by presenting the philosophical proofs that corroborate this superior view.